2016
DOI: 10.1104/pp.16.00092
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Switch of Gene Expression in the Barley Seed Mediated by HvVP1 (Viviparous-1) and HvGAMYB Interactions

Abstract: The accumulation of storage compounds in the starchy endosperm of developing cereal seeds is highly regulated at the transcriptional level. These compounds, mainly starch and proteins, are hydrolyzed upon germination to allow seedling growth. The transcription factor HvGAMYB is a master activator both in the maturation phase of seed development and upon germination, acting in combination with other transcription factors. However, the precise mechanism controlling the switch from maturation to germination progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…We detected differential expression of several barley transcription factors whose roles in germination have been defined by prior studies using alternative methods, including; HvABI5 (HORVU5Hr1G068230), HvVP1/ABI3 (HORVU3Hr1G092690, GAMYB (HORVU3Hr1G079490), HvSAD/DOF23 (HORVU6Hr1G065250), HvWRKY38 (HORVU6Hr1G028790), HvSLN1 (HORVU4Hr1G006930) and HvFUS3 (HORVU3Hr1G067350) (Gubler et al , ; Casaretto and Ho, ; Isabel‐LaMoneda et al , ; Mare et al , ; Moreno‐Risueno et al , ; Abraham et al , ). The abundance of the HvVP1 transcript, a homolog of the Arabidopsis ABA‐regulatory transcription factor ABI3 , was significantly downregulated at later time points (40 and 48 h) in all three organs, consistent with the localization and abundance of this transcript previously determined by RNA in situ hybridization (Abraham et al , ). Furthermore, two of the MYB transcription factors (HORVU0Hr1G018970, HORVU2Hr1G010450) were homologous to Arabidopsis MYBs that regulate germination and root development (Liberman et al , ; Chen et al , ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We detected differential expression of several barley transcription factors whose roles in germination have been defined by prior studies using alternative methods, including; HvABI5 (HORVU5Hr1G068230), HvVP1/ABI3 (HORVU3Hr1G092690, GAMYB (HORVU3Hr1G079490), HvSAD/DOF23 (HORVU6Hr1G065250), HvWRKY38 (HORVU6Hr1G028790), HvSLN1 (HORVU4Hr1G006930) and HvFUS3 (HORVU3Hr1G067350) (Gubler et al , ; Casaretto and Ho, ; Isabel‐LaMoneda et al , ; Mare et al , ; Moreno‐Risueno et al , ; Abraham et al , ). The abundance of the HvVP1 transcript, a homolog of the Arabidopsis ABA‐regulatory transcription factor ABI3 , was significantly downregulated at later time points (40 and 48 h) in all three organs, consistent with the localization and abundance of this transcript previously determined by RNA in situ hybridization (Abraham et al , ). Furthermore, two of the MYB transcription factors (HORVU0Hr1G018970, HORVU2Hr1G010450) were homologous to Arabidopsis MYBs that regulate germination and root development (Liberman et al , ; Chen et al , ).…”
Section: Resultsmentioning
confidence: 89%
“…The abundance of this transcript did not change significantly during germination, indicating that it was present in the scutellum of stored and germinating seeds. Furthermore, ABI3/VP1‐related B3 domain and EIN3‐like transcription factors are known to regulate germination in barley and other plant species (Lopez‐Molina et al , ; Casaretto and Ho, ; Zhang et al , ; Abraham et al , ; Yu et al , ). An AUGMIN subunit‐encoding transcript (HORVU7Hr1G060640) was stored plumule specifically in addition to the transcription factor‐encoding transcripts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the promoter of ONAC026 , SN and NB have an additional stretch of 677 bp, holding multiple copies of DOFCOREZM (AAAG) and EBOXBNNAPA (CANNTG, Figure 3B ), a probable explanation for the higher expression levels in these two accessions ( Figures 2A,D ). EBOXBNNAPA, conserved in many seed storage protein promoters is critical for directing seed-specific expression (Ellerstrom et al, 1996; Ravel et al, 2014), while DOFCOREZM is the recognition core of DOF proteins, reported to activate several storage protein genes (Yamamoto et al, 2006; Abraham et al, 2016). For ONAC023 , the promoter sequences for SN and NB are similar, though there are SNPs amongst the two as well, and hence a similar expression pattern though levels are different.…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory networks are an important aspect of seed development, and often involve formation of homo/heterodimers between TFs. In barley, HvVP1 interacts with HvGAMYB and BPBF and represses their DNA-binding activity (Abraham et al, 2016). Maize OPAQUE2 dimerizes with MADS47 and enhances its activation of zein genes (Qiao et al, 2016).…”
Section: Resultsmentioning
confidence: 99%